Evaluation of Adenosine Deaminase (ADA) Activity for Diagnosis of Tubercular Pleural Effusion (Bangladesh Journal of Medical Biochemistry, 2014)
To find out a sensitive and specific marker for early diagnosis of tubercular pleural effusion, this cross sectional study was carried out in the of National Institute of Diseases of the Chest and Hospital (NIDCH), Dhaka. One hundred and three pleural effusion cases were enrolled in the study. Out of the 103 cases, 62 were tubercular pleural effusion cases and 49 were nontubercular cases. Among the nontubercular cases, 30 cases were due to malignancy, 8 were due to pneumonia and rest 3 cases were due to nephrotic syndrome, congestive cardiac failure and rheumatoid arthritis. Considering 40 U/L as a cut off value for ADA level, the test result was positive in 58 out of 62 patients of tuberculosis indicating sensitivity of the test as 94%; however, among 41 non-tuberculous patients, 5 presented ADA activity level more than 40U/L, which lowers the specificity of the test to 88%. ADA levels were significantly higher in tuberculous than in nontuberculous cases (p value